First description of comb-tailed spiders (Araneae: Hahniidae) from Vietnam - Zhang, Zhi-Sheng; Li, Shuqiang; Pham, Dinh-Sac (Zootaxa, 2013)
Spider family Hahniidae was firstly recorded from Vietnamin the present paper. In total, three genera and five species were recorded in three national parks of Northern Vietnam: Alistra hamata sp. nov. (male), Hahnia himalayaensis Hu & Zhang, 1990 (male, female), H. rimiformis sp. nov. (male, female), H. zhejiangensis Song & Zheng, 1982 (male, female) and Scotospilus longus sp. nov. (male, female). Morphological illustrations and photos of new species as well as descrip-tions and copulatory organs’ photos of known species are given. The genus Scotospilus and the position of S. longus sp. nov. are discussed.